2015
DOI: 10.1590/s0004-28032015000300016
|View full text |Cite
|
Sign up to set email alerts
|

GAMMA GLUTAMYLTRANSFERASE IMPACT IN THERAPEUTIC RESPONSE OF CHRONIC HEPATITIS C: a systematic review of the literature

Abstract: -Background -The standard treatment of chronic hepatitis C is the administration of pegylated interferon α2a or α2b in combination with ribavirin, but adverse effects can be observed, as well as the high cost of this therapy. Therefore, there is interest in understanding the predictors of sustained virologic response, as the gamma glutamyltransferase. Objective -To evaluate the serum levels of gamma glutamyltransferase as a predictor of response to treatment with pegylated interferon α and ribavirin in chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Of these, GGT ≥ 56 U/L showed the highest aHR at 4.157 (95%CI 1.400–12.350, p = 0.0103). GGT is an enzyme located on the outer surface of cell membranes in the liver, kidney, biliary tract, intestines, heart, spleen, pancreas and brain 40 . It catalyses the transfer of gamma‐glutamyl groups from glutathione to amino acids and dipeptides.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, GGT ≥ 56 U/L showed the highest aHR at 4.157 (95%CI 1.400–12.350, p = 0.0103). GGT is an enzyme located on the outer surface of cell membranes in the liver, kidney, biliary tract, intestines, heart, spleen, pancreas and brain 40 . It catalyses the transfer of gamma‐glutamyl groups from glutathione to amino acids and dipeptides.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that serum GGT activity is directly proportional to the level of oxidative stress 41 . Elevated serum GGT activity is associated with increased overall mortality and an elevated risk of cardiovascular complications, diabetes, arterial hypertension and cancer, especially that involving the prostate, breast and liver 40 . GGT is also used in the diagnosis of liver conditions, mainly alcohol‐related and cholestatic liver diseases 42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations